ChemInform Abstract: Amino Acid Salts Catalyzed Asymmetric Aldol Reaction of Tryptanthrin: A Straightforward Synthesis of Phaitanthrin A (V) and Its Derivatives. Issue 7 (18th February 2014) - Kang, Guowei; Luo, Zhenli; Liu, Chongxing; Gao, Hang; Wu, Quanquan; Wu, Huayue; Jiang, Jun
Abstract The first asymmetric synthesis of the title compound (V) is achieved on a gram‐scale.